The role of recombination variability to the formation of the population the HIV‐1 population circulating in the Primorsky Krai, Russia - M. R. Halikov; V. E. Ekushov; A. V. Totmenin; L. G. Gotfrid; L. F. Sklyar; N. P. Soloveva; E. N. Serdtseva; M. I. Shportova; Zh. A. Martynchenko; S. N. Beniova; S. A. Ermolickaja; I. S. Gorelova; et al. (Юг России: экология, развитие)
Aim. To research the molecular epidemiological features of the territorial spread of HIV infection and the influence of recombination variability on the formation of the HIV‐1 population in the Primorsky Krai, Russia.   Materials and Methods. A comprehensive analysis of the molecular genetic characteristics of HIV‐1 and clinical‐epidemiological data of 127 HIV‐infected residents of Primorsky Krai was performed. The nucleotide sequences of the pol gene region encoding protease, reverse transcriptase and integrase of HIV‐1 were obtained by the sequencing of amplified fragments of the virus. Genotyping, phylogenetic, and mutational analyses were performed using specialised software resources.   Results. In the samples studied of HIV‐1 isolated in the Primorsky Krai, the dominance of HIV‐1 subtype A6 was detected as 40.9 %. The prevalence of subtype B viruses is high compared to other Russian regions – 29.9 %. The HIV‐1 subtype C was found in 6.3 % of the samples studied; circulating recombinant forms CRF63_02A6 – 6.3 %, CRF02_AG – 0.8 %. Unique viruses resulting from the recombination of HIV subtypes A6 and B, A6 and C, C and B were found in 15.7 % of cases (URF_A6C, URF_CB, URF_BA6). Of the 18 HIV‐1 URFs described, 14 were variants of URF_A6C (11 %). Analysis of the near full‐length genome (NFLG) of URF_A6C made it possible to find and describe a new HIV genovariant spreading in Primorye ‐ CRF157_A6C.   Conclusion. The analysis of HIV‐1 circulating in the Primorsky Krai confirmed that a specific molecular epidemic situation is developing in the region, which is characterized by active transmission of viruses not only of subtype A6, but also of subtypes B and C, which is not observed in other regions of Russia. For the first time in the Far East, a high frequency of HIV‐1 new unique recombinant forms occurrence has been described, some variants of which are beginning to spread among residents of the Primorsky Krai. An increase in the genetic heterogeneity of the viral population due to recombination variability of HIV is a negative prognostic factor for the territorial epidemic progress of HIV infection in the Far East.